A Scoping Review of Text-Matching Software Used for Student Academic Integrity in Higher Education. (21st September 2021) - Hayden, K. Alix; Eaton, Sarah Elaine; Pethrick, Helen; Crossman, Katherine; Lenart, Bartlomiej A.; Penaluna, Lee-Ann
Abstract : Text-matching software has been used widely in higher education to reduce student plagiarism and support the development of students' writing skills. This scoping review provides insights into the extant literature relating to commercial text-matching software (TMS) (e.g., Turnitin) use in postsecondary institutions. Our primary research question was "How is text-matching software used in postsecondary contexts?" Using a scoping review method, we searched 14 databases to find peer-reviewed literature about the use of TMS among postsecondary students. In total, 129 articles were included in the final synthesis, which comprised of data extraction, quality appraisal, and the identification of exemplar articles. We highlight evidence about how TMS is used for teaching and learning purposes to support student success at the undergraduate and graduate levels.